(untitled) (ResearchJet Journal of Analysis and Inventions, 2021)
The article examines the role of reading as a type of speech activity in teaching foreign languages in a non-linguistic university. Much attention is paid to the main types of reading, their classification and brief description are given. The article emphasizes the importance of developing flexible reading skills in students using modern computer technologies.